Cutting-edge virtual reality - Peterson, Christy (Searchlight books. Cutting-edge STEM., 2019)
Briefly explores the history and current capabilities of virtual reality technology, which can let users experience a video game in first person or make them feel like they are visiting Antarctica from the comfort of their living rooms. Includes a glossary.